Biological Motor To Move Loads At Microscales-Kinematic Analysis - Ng, Chyi Sean (Universiti Sains Malaysia, 2017)
Magnetic force was introduced as one of the method to control the motion of microalgae. To make the microalgae become magnetically responsive, the cation polymer binder, poly (diallyldimethylammonium chloride) (PDDA) was used to promote the effective attachment of iron oxide nano particles (IONPs) onto the surface of microalgae, Clamydomonas Reinhardtii species (CR species) through electrostatic interaction. From the experiment, it was found that the swimming velocity of fresh CR species species is within 100 ᶙm/s to 128 ᶙm/s. Next, after the attachment of PDDA functionalized IONPs, the swimming velocity of CR species reduced drastically to only about 9 ᶙm/s to 29 ᶙm/s which around 75.23% to 91.79% of reduction from the average velocity of free moving CR species. This is because motion of the flagella is being distorted by PDDA functionalized IONPs. According to law of conservation of momentum, when IONPs attached to the microalgae, the increase in total mass caused its swimming velocity reduced. Lastly, when magnetic force is applied, the swimming velocity of targeted CR species with PDDA functionalized IONPs increased significantly with an increment vary from 64.65% to 334.83% of its original swimming velocity. The movement of microalgae is directed toward the source of magnetic force.